Alcohol Consumption and Bone Mineral Density in People with HIV and Substance Use Disorder: A Prospective Cohort Study. (25th June 2018) - Saitz, Richard; Mesic, Aldina; Ventura, Alicia S.; Winter, Michael R.; Heeren, Timothy C.; Sullivan, Meg M.; Walley, Alexander Y.; Patts, Gregory J.; Meli, Seville M.; Holick, Michael F.; Kim, Theresa W.; Bryant, Kendall J.; et al.
Abstract : Background: People living with HIV (PLWH) commonly have low bone mineral density (BMD) (low bone mass and osteoporosis) and are at high risk for fractures. Fractures and low BMD are significant causes of morbidity and mortality, increasingly relevant as PLWH age. Alcohol use is common among PLWH and known to affect bone health. The association between alcohol use and changes in BMD among PLWH is not well understood. Methods: We conducted a 3.5‐year prospective cohort study of 250 PLWH with substance use disorder or ever injection drug use. Annual alcohol consumption was measured as a mean of grams per day of alcohol, mean number of heavy drinking days per month, mean number of days abstinent per month, and any heavy drinking, using the 30‐day Timeline Followback method twice each year. The primary outcome was annual change in BMD measured each year by dual energy X‐ray absorptiometry in grams per square centimeter (g/cm 2 ) at the femoral neck. Additional dependent variables included annual change in total hip and lumbar spine BMD, >6% annual decrease in BMD at any site, and incident fractures in the past year. Regression models adjusted for relevant covariates. Results: The median age of participants was 50 years. The median duration of HIV infection was 16.5 years and the mean time since antiretroviral therapy initiation was 12.3 years. At study entry, 67% of participants met criteria for low BMD (46% low bone mass, 21% osteoporosis). Median follow‐up was 24 months. We found no significant associations between any measure of alcohol consumption and changes in BMD (g/cm 2 ) at the femoral neck (adjusted β for g/d of alcohol = −0.0032, p  = 0.7487), total hip, or lumbar spine. There was no significant association between any measure of alcohol consumption and >6% annual decrease in BMD at any site, or incident fractures. Conclusions: In this sample of PLWH and substance use disorders or ever injection drug use, we detected no association between any of the alcohol measures used in the study and changes in BMD or incident fractures. Abstract : Although we cannot conclude alcohol is safe for bone, in part because of difficulty isolating its effects among many others, in people with HIV infection and substance use disorder, there was no association between alcohol use and fractures or changes in bone density.